In vitro germination and viability of pea pollen grains after application of organic nano-fertilizers (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
The objective of this study was to evaluate the influence of two organic nanofertilizers,Lithovit and Nagro, on in vitro germination, pollen tube elongation and pollen grain viability of Pisum sativum L cv. Pleven 4. The effect of their application was high and exceeded data for the untreated control (44.2 and 47.23 % regarding pollen germination and pollen tube elongation, respectively), as well as the effect of the control organic algal fertilizer Biofa (17.5 and 27.9 %, respectively). Pollen grains were inoculated in four culture media. A medium containing 15% sucrose and 1% agar had the most stimulating impact on pea pollen grains. Pollen viability, evaluated by staining with 1% carmine, was within limits of 74.72-87.97%. The highest viability of pollen grains was demonstrated after the application of Nagro organic nano-fertlizer.
Keywords: Organic fertilizers; Pollen; Germination; Peas